2006
DOI: 10.1002/maco.200503901
|View full text |Cite
|
Sign up to set email alerts
|

High temperature corrosion of structural materials under gas‐cooled reactor helium

Abstract: The Generation IV International Forum has selected six promising nuclear power systems for further collaborative investigations and development. Among these six concepts, two candidates are Gas Cooled Reactors (GCR), namely the Very High Temperature Reactor (VHTR) and the Gas-cooled Fast Reactor (GFR). The CEA has launched a R&D program on the metallic materials for application in an innovative GCR. Structural GCR alloys have been extensively studied in the past three decades. Some critical aspects for the ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Similar decarburization also was observed in other alloys such as Inconel 617 and Haynes 230. [32][33][34]36,[46][47][48] The measurements also indicate that A2 alloy was decarburized rapidly within the first 10 to 15 hours of exposure with the sample at 50 hours exposure showing complete carbon loss. However, the rate of decarburization was slower in the carbide-containing A8 alloy.…”
Section: B Bulk Carbon Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Similar decarburization also was observed in other alloys such as Inconel 617 and Haynes 230. [32][33][34]36,[46][47][48] The measurements also indicate that A2 alloy was decarburized rapidly within the first 10 to 15 hours of exposure with the sample at 50 hours exposure showing complete carbon loss. However, the rate of decarburization was slower in the carbide-containing A8 alloy.…”
Section: B Bulk Carbon Analysismentioning
confidence: 98%
“…The fact that Cr 2 O 3 is not seen on the surface is indicative of the kinetics of the chromia-assisted decarburization reaction Cr 2 O 3 (s) + 3C alloy (ss) fi 2Cr (ss) + 3CO(g). [34,[36][37][38] Since it has been shown earlier that, in the presence of a pre-grown Cr 2 O 3 , all of the carbon in the alloy (0.08 wt pct) is removed within 50 hours, the formation of Cr 2 O 3 must be the rate-limiting step since the alloy carbon content in the as-fabricated alloys was still 0.045 wt pct after decarburizing for 25 hours. In other words, the fast diffusing carbon is readily available at the alloy surface whereas the growth of chromium oxide occurs at a slower pace.…”
Section: Rate Limiting Step: Formation Of Cr 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reviews published data [4][5][6][7][8][9][10][11] that deal with the corrosion resistance of candidate high temperature metallic alloys, Alloys 617 and 230, in the specific environment of the reactor primary circuit. It is shown that the reactive impurities H 2 O, CO, H 2 , and CH 4 in the cooling gas interact with Ni alloys at high temperature causing corrosion effects that can significantly influence the in-depth microstructure, and consequently the mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The helium inevitably contains parts per million (ppm) level of CO, CO 2 , H 2 , H 2 O, and CH 4 as impurities, which arise mainly from reactions between the hot graphite core and in-leakage of O 2 , N 2 , and water vapor from seals, welds, and degassing of reactor materials such as fuel, thermal insulation, and in-core structural materials. [4,5] Typical concentrations of helium impurities in various gascooled reactors are shown in Table I.…”
Section: Introductionmentioning
confidence: 99%